The Internet, social media and citizen politics - Zhu, Junyan (2021)
At the heart of democratic processes, political participation is fundamental for many social and political goals. When new communication mediums emerge, we wonder to what extent it influences political participation, whether it affects various social groups in an equal manner, which socioeconomic groups benefit more from the use of new information technology, and what the implications are for democracy. With these broad questions in mind, this thesis systematically examines the meaning for citizen politics from the use of the Internet and social media for political purposes. Specifically, the empirical papers assess the impact of Internet usage on civic competence, how social media influences citizenship by shaping effective political participation and social capital, and individual reception to online misinformation. The analyses build upon existing literature on the effect of social media use and provide novel insights into the conceptual and methodological development of the scholarly debate on the digital divide. The findings reveal that the opportunities and the challenges from digital use have different practical meanings and consequences based on social group. Individuals with more education, income, and political knowledge are better equipped than others to effectively use the Internet and social media for information and political participation and are less receptive to online misinformation. The results find more support for reinforcement effects between digital media use and political participation. Taken together, these findings suggest that we should not overstate the capability of information and communications technology, which alone cannot achieve the democratic goal of digital equality and an informed citizenry.